2008
DOI: 10.1186/1471-2377-8-37
|View full text |Cite
|
Sign up to set email alerts
|

The effect of coaching on the simulated malingering of memory impairment

Abstract: Background: Detecting malingering or exaggeration of impairments in brain function after traumatic brain injury is of increasing importance in neuropsychological assessment. Lawyers involved in brain injury litigation cases routinely coach their clients how to approach neuropsychological testing to their advantage. Thus, it is important to know how robust assessment methods are with respect to symptom malingering or exaggeration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 35 publications
1
13
2
Order By: Relevance
“…The WCT has the advantage of being relatively new and not widely known in the medico-legal setting. Currently, little information about the test is available via the Internet, unlike the detailed information relating to the TOMM, which is readily available on the Internet and in books and is well known by attorneys (Bauer & McCaffrey, 2006;Brennan et al, 2009;Russler et al, 2008). Further, Miller and colleagues (2011) demonstrated that the WCT added incremental value to the predictive accuracy of the Wechsler Memory ScaleFourth Edition.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The WCT has the advantage of being relatively new and not widely known in the medico-legal setting. Currently, little information about the test is available via the Internet, unlike the detailed information relating to the TOMM, which is readily available on the Internet and in books and is well known by attorneys (Bauer & McCaffrey, 2006;Brennan et al, 2009;Russler et al, 2008). Further, Miller and colleagues (2011) demonstrated that the WCT added incremental value to the predictive accuracy of the Wechsler Memory ScaleFourth Edition.…”
Section: Discussionmentioning
confidence: 94%
“…It has been reported that a large number of attorneys routinely coach their clients on how to approach neuropsychological tests (Brennan et al, 2009;Jelicic, Ceunen, Peters, & Merckelbach, 2011;Powell et al, 2004;Russler, Brett, Klaue, Sailer, & Munte, 2008;Suhr & Gunstad, 2007). Studies investigating the effects of coaching on the TOMM found that although coaching reduced the incidence of detection, the TOMM still detected 80% to 87% (Jelicic et al, 2011) and 93% to 96% (Powell et al, 2004) of coached TBI simulators.…”
mentioning
confidence: 97%
“…Bias-97 (CARB-97) and Word Memory Test (Dunn, Shear, Howe, & Ris, 2003), Rey's 15-Item Test and Dot Counting Test (Erdal, 2004), Portland Digit Recognition Test (Gunstad & Suhr, 2001), Category Test (DiCarlo, Gfeller, & Oliveri, 2000), Medical Symptom Validity Test and the Amsterdam Short-Term Memory Test (Merten, Green, Henry, Blaskewitz, & Brockhaus, 2005), and Short-Term-Memory Test from the Bremer Symptom-Validierung (Russeler, Brett, Klaue, Sailer, & Munte, 2008). Coached malingering was difficult to detect using these various tests.…”
Section: Studies Have Investigated the Effect Of Coaching On Various mentioning
confidence: 99%
“…In instances where litigation is involved, lawyers may instruct their clients about PVTs (Lezak, Howieson, Bigler, & Tranel, ). Studies have investigated the effect of coaching on various types of malingering tests, such as Computerized Assessment of Response Bias‐97 (CARB‐97) and Word Memory Test (Dunn, Shear, Howe, & Ris, ), Rey's 15‐Item Test and Dot Counting Test (Erdal, ), Portland Digit Recognition Test (Gunstad & Suhr, ), Category Test (DiCarlo, Gfeller, & Oliveri, ), Medical Symptom Validity Test and the Amsterdam Short‐Term Memory Test (Merten, Green, Henry, Blaskewitz, & Brockhaus, ), and Short‐Term‐Memory Test from the Bremer Symptom‐Validierung (Russeler, Brett, Klaue, Sailer, & Munte, ). Coached malingering was difficult to detect using these various tests.…”
Section: Introductionmentioning
confidence: 99%
“…Is the SVT measure infallible? DenBoer and Hall (2007) have shown that simulators can be “taught” how to detect SVT tasks and pass them and go on to fail the more formal neuropsychological measures (see also Rüsseler, Brett, Klaue, Sailer, & Munte, 2008). If the SVT task can be faked how would the clinician and/or researcher know?…”
Section: The Problem With Cut Scoresmentioning
confidence: 99%